Dynamic analysis of automotive carbon fiber strut bar / Mohd Suffian Ab Razak - Mohd Suffian, Ab Razak (2018)
Front strut bar is an automotive part commonly used for McPherson suspension system to minimize load on the strut tower by tying both left and right strut with a single bar. By distributing the force acting on a single strut to both strut tower, the strut bar reduces the chassis flex which improves ride and handling especially during cornering. Therefore, strut bar should be stiffer but lighter at the same time to reduce vehicle weight towards fuel efficiency and lower carbon emission. This research attempts to design a lightweight carbon fiber reinforced polymer strut bar in order to replace conventional steel strut bar with equivalent stiffness. For validation, a steel strut bar model is analyzed by conducting experimental modal analysis to determine their natural frequencies and the corresponding mode shapes. These results were compared to analytical and simulation results. Later, the dynamic behavior of CFRP and the corresponding mode shapes were analyzed and correlated with static loading test results. Findings in the dynamic analysis will be used as input in designing a carbon fiber strut bar to further optimizes using composite optimization method in Hyperworks Optistruct until desired characteristics are obtained. The dynamic analysis found out that alternate positive-negative degree ply angle arrangement could resist resonance due to torsion. Combination of different ply orientation and stack sequence results in the design of an optimized carbon fiber strut bar achieved a reduction in weight, higher natural frequency while improving or preserving the static and dynamic performances. Keywords: composite strut bar, ply orientation, composite optimization, dynamic analysis, experimental modal analysis (EMA), finite element analysis (FEA) iv